Strategy For Revitalizing Lempe Tourism Objects In Improving The Economy Of The Lolai Community - Stefani Marina Palimbong; Rahma Gusmawati Tammu; Ratten Palungan (Jurnal Ekonomi, 2024)
This research aims to determine the strategy of Revitalizing Lempe Tourism Objects in Improving the Economy of the Lolai Community. The problem in this study is How is the strategy of Revitalizing Lempe Tourism Objects in Improving the Economy of the Lolai Community? The results show that the IFAS value is greater than the EFAS value, this shows that the strength possessed can still create opportunities and overcome threats. Lempe Lolai tourist attraction can still develop its business with its internal strength. The appropriate revitalization strategy used by Lempe Lolai tourist attractions is the SO (Strengths-Opportunity) strategy such as revitalizing the surrounding natural area in the form of greening the surrounding area, revitalizing facilities, especially with modern style and architecture and physical revitalization of lodging, completeness of facilities and social revitalization by improving service quality.